A STUDY OF THE SPEAKING LEARNING STRATEGIES USED BY ENGLISH EDUCATION DEPARTMENT STUDENTS - Eka Wahyu Saputra; Nanang Bagus Subekti (Universitas Sarjanawiyata Tamansiswa, 2017)
English is the world language. There are four skills in English such as listening, reading, speaking, and writing. Based on the Competence-Based Curriculum, speaking is one of the four basic competences that the students should gain well.Â Meanwhile, developing speaking skills needs strategies or ways to make them easier to learn. This article describes the speaking learning strategies which were used by the English language students. The subjects of this study were the English language students of the fourth semester in English Education Study Program, Faculty of Teacher Training and Education of Sarjanawiyata Tamansiswa University, Yogyakarta. The data were collected through questionnaire and interview. This study used mix method and descriptive qualitative technique of analysis study which covered reducing data, displaying data and drawing data conclusion. The results from the analysis showed that almost all of the strategies proposed by Oxford (1990) were used by the students such as memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. Moreover, it showed significant correlation between the speaking learning strategies used by the students and the result of assessment.